Repeated-Dose Pharmacokinetics of Inhaled Ciclesonide (CIC-HFA) in Japanese Children with Bronchial Asthma: A Phase I Study - Takahide Teramoto (Allergology International, 2012)
Background: Ciclesonide (CIC) is a highly safe, inhaled corticosteroid (ICS) that is converted into a pharmacologically active metabolite (des-isobutyryl-ciclesonide); this metabolite, in turn, exerts a local antiinflammatory effect on lung tissue. The present study was undertaken to analyze the pharmacokinetics of desisobutyryl-ciclesonide in the serum of Japanese children with bronchial asthma treated by repeated doses of CIC and to compare the data thus obtained with those obtained for Caucasian children with bronchial asthma. Methods: Eight Japanese children with bronchial asthma were treated for 7 days with CIC-hydrofluoroalkalane (CIC-HFA) 200 Mg/day administered by a metered-dose inhaler. The study was designed to assess the pharmacokinetics after 7-day repeated administration by which the steady state can be achieved, based on the results of an earlier study involving healthy Japanese adult males who received 7-day repeated administration of CIC-HFA. Blood was sampled at multiple time points on Day 7 of treatment for measurement of the serum des-isobutyryl-ciclesonide level. Results: The pharmacokinetic parameters (AUC from time zero to last observed concentration [AUCt], AUC over the dosage interval τ at steady state [AUCss], maximum concentration [Cmax], and terminal elimination halflife [T1/2]) and the temporal changes in the serum levels of des-isobutyryl-ciclesonide after repeated administration of CIC-HFA (200 μg/day) in Japanese children with bronchial asthma differed only slightly from those in Caucasian children with bronchial asthma. No serious adverse events were noted during the study period. Additionally, no abnormalities were detected in the serum cortisol level, other laboratory parameters, or vital signs. Conclusions: Our results suggest that there is little difference in the pharmacokinetics of des-isobutyrylciclesonide up on repeated administration of CIC-HFA between Japanese and Caucasian children with bronchial asthma. And our study suggests that CIC-HFA (200 μg/day, once daily) can be administered safely for 7 days, without raising any safety concerns.